Can we predict and take a proper treatment for postpartum pulmonary embolism? A single institution review of five cases - Soo-Ho Chung; Chang Woo Choi; Jae Hong Sang (Clinical and Experimental Obstetrics & Gynecology)
Postpartum pulmonary embolism (PPE) is a rare disorder in the puerperium that can present a wide range of symptoms after childbirth. This condition can lead to death and is the most common cause of maternal mortality, accounting for about 10% of all maternal deaths in the United States. A previous study conducted over 3 years (2014-2016) followed five patients diagnosed with postpartum pulmonary embolism, two of whom died. As PPE is characterized by a variety of symptoms, patients suspected of this condition require prompt diagnosis and treatment. Based on the previous investigation of five patients, the present study aimed to elucidate considerations for early treatment and diagnosis. Maternal mortality can be minimized by proper treatment and early detection using contrast-enhanced chest computerized tomography and echocardiography in women during or after delivery, particularly those with suspected embolism.